Positive Politeness Strategies in Blackpink’s Interview with Jimmy Kimmel 2020 - Muhammad Luthfi Ramdhan; Luh Gayatri Sintadevi; Faisal (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
Positive politeness strategies remain relevant in modern society as essential tools for fostering harmony and mutual respect in social interactions. In today’s media landscape, public figures particularly those with significant popularity are expected to demonstrate appropriate attitudes, effective communication skills, and positive body language, especially during public appearances such as talk show interviews. This study investigates the use of positive politeness strategies by the members of Blackpink during their appearance on the American talk show Jimmy Kimmel Live. Adopting Brown and Levinson’s politeness theory as the primary framework, this research aims to identify, classify, and comprehensively describe the positive politeness strategies employed by the group. The findings reveal that the verbal and non-verbal expressions demonstrated by Blackpink align with the positive politeness strategies outlined by Brown and Levinson. Furthermore, this study extends the analysis to the 2020 documentary Blackpink: Light Up the Sky, offering additional insights into how positive politeness is manifested in various media contexts. Through a detailed qualitative examination, this research contributes to a deeper understanding of interpersonal communication dynamics and the role of politeness in the public representation of global celebrities.